Tinjauan Teologis terhadap Tradisi Kawin Tangkap di Pulau Sumba–Nusa Tenggara Timur - Johanis Putratama Kamuri; Grace Mariany Toumeluk (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. This paper aimed to determine the theological position of Christians towards the tradition of kawin tangkap (bride kidnapping or bridenapping) on Sumba Island. Kawin tangkap is a tradition of kidnapping woman to make her a bride. The tradition has become a social problem for the government and society, especially the Sumbanese women. Through hermeneutic approach, this research analyzes the tradition of kawin tangkap in Marapu’s perspective to determine the proper outlook of the church. The conceptual framework in the analysis was the concept of Christian marriage and the story of abducted wives in Judges 21. Through this analysis it was found that kawin tangkap is a tradition that opposes the Bible's teachings on marriage, a sign of spiritual decline, and the violence against women.Abstrak. Tulisan ini bertujuan menentukan sikap teologis orang Kristen terhadap tradisi kawin tangkap di Pulau Sumba. Kawin tangkap adalah tradisi penculikan perempuan untuk dijadikan isteri. Tradisi kawin tangkap menjadi masalah sosial yang meresahkan pemerintah dan masyarakat, khususnya kaum perempuan. Melalui pendekatan hermeneutis penelitian ini menganalisis tradisi kawin tangkap dalam perspektif Marapu untuk menentukan sikap gereja. Bingkai konseptual dalam analisis adalah konsep perkawinan dalam perspektif Kristen dan kisah penangkapan perempuan untuk dikawini dalam Hakim-hakim 21. Melaluinya ditemukan bahwa kawin tangkap adalah tradisi yang menentang ajaran Alkitab tentang perkawinan, tanda kemerosotan spiritual, dan merendahkan martabat perempuan.